Yield of Fodder Maize (Zea mays) and its Chemical Composition under Varying Plant Densities and Nutrient Management - Subrahmanya, D. J.; Kumar, Rakesh; Tyagi, Nitin; Ram, Hardev; Singh, Magan; Meena, R. K.; Tamta, A.; Pandey, A. K. (Indian Journal of Animal Nutrition, 2017)
An experiment consisting of four plant densities (45, 60, 75 and 90 kg/ha seed rate) and five fertilizer levels (0, 50, 75, 100 and 125% recommended dose of fertilizers; RDF) was laid out in split plot design to find out the yield and chemical composition of fodder maize (Zea mays L.). Application of 60 kg/ha seed rate increased (P<0.05) the green fodder yield (543.32 q/ha) which was 19% higher than 45 kg/ha seed rate. Likewise, green fodder yield increased (P<0.05) upto 637.0 q/ha at 125% RDF. Application of 60 kg/ha seed rate increased (P<0.05) the DM yield (121.03 q/ha). The DM yield of the fodder maize at harvest increased (P<0.05) upto 140.98 q/ha with the application of 125% RDF over control. The interaction effect on DM yield was noticed between plant density and nutrient management at harvest. The maximum DM yield of 148.7 q/ha was observed at 60 kg/ ha seed rate with 125% of RDF. The highest CP content of 9.84% was observed when seed rate of 45 kg/ha was used. The CP content increased (P<0.05) with increase in application of fertilizer up to 125% RDF over control. The EE content was not affected by seed rate. Increase in nutrient levels resulted in increase (P<0.05) in EE content up to 125% RDF. The maximum EE level of 1.84% was observed at 125% of RDF. The contents of NDF and ADF were lowest at 45 kg/ha seed rate and increased with the increase in seed rate. The levels of NDF and ADF were the lowest at 125% RDF. Therefore, combination of 60 kg/ha seed rate and 125% RDF was effective treatment in terms of both yield and chemical constituents of fodder maize.